How social media influencers impact travel behaviors: the effects of authenticity and social contagion in experiential consumption - Alves, Rita da Costa Nunes Malcata (2020)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Marketing Intelligence